TERMS AND THE USAGE OF LINGOCULTURAL TERMS IN LANGUAGES (TAMADDUN NURI JURNALI, 2024)
This article analyses  the works devoted to the research of language and speaker (listener), language and communication, language and logic, language and knowledge of the world, language and culture are analyzed in the direction of linguo-cultural studies.